2009
DOI: 10.1007/s00405-009-0927-6
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular functions in motion sickness susceptible individuals

Abstract: There exists no functional guide that can serve as a diagnostic tool for individual susceptibility to motion sickness (MS). We evaluated vestibular system functioning via a caloric test (which assesses functioning of the superior vestibular nerve) and the vestibular-evoked myogenic potentials (VEMP) test (which assesses inferior vestibular nerve functioning) in 20 MS susceptible and 20 nonsusceptible individuals. Susceptibility to MS was determined by self-declaration and with MS susceptibility questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
19
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
7
19
1
2
Order By: Relevance
“…The results revealed no difference between the groups for cVEMP and oVEMP amplitudes. The findings of the present study are in agreement with those by Tal et al (2007) and Buyuklu, Tarhan and Ozluoglu (2009) for cVEMP and Xie et al (2012) for oVEMP. However, these findings are in dissonance with those reported by Tal et al (2006).…”
Section: Discussionsupporting
confidence: 96%
See 3 more Smart Citations
“…The results revealed no difference between the groups for cVEMP and oVEMP amplitudes. The findings of the present study are in agreement with those by Tal et al (2007) and Buyuklu, Tarhan and Ozluoglu (2009) for cVEMP and Xie et al (2012) for oVEMP. However, these findings are in dissonance with those reported by Tal et al (2006).…”
Section: Discussionsupporting
confidence: 96%
“…The findings of present study are in agreement with those reported previously (Tal et al 2006(Tal et al , 2007Buyuklu, Tarhan, and Ozluoglu 2009). Although they did not use PD as a separate group, they reported a lack of significant difference in the latencies of cVEMP between MS and NS.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…They found that the group susceptible to seasickness exhibited a signifi cantly higher cVEMP threshold and a signifi cantly lower peak-to-peak P13-N23 amplitude interval compared with the group not susceptible to seasickness. However, in contrast to their study, Buyuklu et al ( 5 ) did not fi nd a statistically signifi cant difference in cVEMP parameters of subjects between MS susceptible individuals and non-MS susceptible individuals. Their fi ndings appear not to support saccular otolith function asymmetry in MS patients.…”
mentioning
confidence: 88%